2010
DOI: 10.1200/jco.2009.25.3187
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab As Single-Agent CD20 Immunotherapy in Fludarabine-Refractory Chronic Lymphocytic Leukemia

Abstract: Patients and MethodsPatients received eight weekly infusions of ofatumumab followed by four monthly infusions during a 24-week period (dose 1 ϭ 300 mg; doses 2 to 12 ϭ 2,000 mg); response by an independent review committee (1996 National Cancer Institute Working Group criteria) was assessed every 4 weeks until week 24 and then every 3 months until month 24. Results This planned interim analysis included 138 treated patients with FA-ref (n ϭ 59) and BF-ref (n ϭ 79)CLL. The overall response rates (primary end po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
350
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(376 citation statements)
references
References 32 publications
(2 reference statements)
19
350
2
5
Order By: Relevance
“…Thus, an interim analysis in an international phase I trial of ofatumumab, used as single agent at a dose of 2000 mg in refractory CLL patients, reported a good safety profile and a high overall response rate in heavily pretreated patients. 40 A multicenter phase I study of GA-101, used as single agent at escalating doses of 400-2000 mg, showed good responses with two cases of complete remission at intermediate doses (800/1200 mg), a tumor-burden decrease and good tolerance in 11/13 evaluable CLL patients. 41 Finally, an ongoing phase I study is testing LFB-R603 at doses escalating from 75 to 1650 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an interim analysis in an international phase I trial of ofatumumab, used as single agent at a dose of 2000 mg in refractory CLL patients, reported a good safety profile and a high overall response rate in heavily pretreated patients. 40 A multicenter phase I study of GA-101, used as single agent at escalating doses of 400-2000 mg, showed good responses with two cases of complete remission at intermediate doses (800/1200 mg), a tumor-burden decrease and good tolerance in 11/13 evaluable CLL patients. 41 Finally, an ongoing phase I study is testing LFB-R603 at doses escalating from 75 to 1650 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The humanized anti-CD20 antibody ofatumumab was recently approved for the treatment of fludarabine-and alemtuzumab-refractory patients, resulting in 58% OR and a median PFS of 5.7 months. However, this antibody showed little benefit in fludarabine-refractory patients harboring the 17p deletion and bulky lymphadenopathy (OR 14%) [8]. Therapy with HDMP, with or without anti-CD20 antibody rituximab, was shown to be effective in refractory CLL [9][10][11], including cases with the TP53 mutation, with reported OR of 69% and median PFS of 12 months [12].…”
Section: Introductionmentioning
confidence: 99%
“…Like in the dose-escalating study cited above, the most common adverse events were infusion reactions and infectious complications. Efficacy was lower in CLL with 17p deletion [19].…”
Section: Figurementioning
confidence: 89%